To find the general solution of this differential equation and the particular solution through the aforementioned circle.
The corresponding symmetric system for the equation is
and you need 2 independent first integrals.
Adding all numerators and denominators we get
what means
"d(x + y + z) = 0" , so the "1^{st}" independent integral is "f\u2081 = x + y + z."
Next "\\frac{(dx - dy + dz)}{(x - y - y + x + z + z)} = \\frac{dz}{z}" yields
and we get the "2^{nd}" independent integral "f\u2082 = \\frac{x - y + z}{z\u00b2}"
According the theory of 1st order linear non-homogeneous partial differential equations the general solution in implicit form is "\u03a6((x - y + z)\/z\u00b2, x + y + z) = 0" , here Φ is a differentiable function of 2 variables, or (x - y + z)/z² = φ(x + y + z), where φ is an arbitrary differentiable function of 1 variable.
Now we must determine φ to satisfy the initial condition. For z = 1 we get
x - y + 1 = φ(x + y + 1). If x + y + 1 = t and y = ±√(1 - x²), then
φ(t) = 1 ± √(1 + 2t - t²), finally
(x - y + z)/z² = 1 ± √(1 + 2(x+y+z) - (x+y+z)²) or
(x - y +z - z²)² = z⁴(1 + 2(x + y + z) - (x + y + z)²) in implicit form.
Comments
Leave a comment